Landscape hazards, Hamlet of Arviat, Nunavut - D.L. Forbes; T. Bell (Polar Data Catalogue, 2010)
The map was developed using QuickBird high-resolution satellite imagery supported by ground observations over several days in July 2009. This landscape hazards map was derived from the surficial geology map through a hazards classification of surficial units. This is a map of ground conditions in areas classified as low-, medium-, or high-risk sites for future development. It is intended to help in understanding natural hazards and potential impacts of climate change, to support community development planning and climate-change adaptation